Linking Invertebrate Microbiomes To Host Evolutionary Trajectory: A Case Study Of The Nacellid Limpet Holobionts Across Different Provinces Of The Southern Ocean. - Schwob, Guillaume Julien (2025)
The ecological and evolutionary dynamicsbetween microbiomes and animals, mainlyvertebrates,have been extensively studied over the last decades, driven bythe exponential development of next-generation sequencing. Thefitness of various eukaryotic hosts has been shown to strongly rely on their associated microbial communities, leading to the rise of the concept of holobiont. This paradigm redefinesindividualsas biologicallycomplex systems comprising bothhost genomesand theirmicrobiomes. The phenotypic plasticity of holobionts, largely determined by their microbiomes, is crucialforrapid adaptationtochangingenvironmental conditions. Understanding the adaptive traits of holobionts is critical, especially for the conservation of holobiont populations in an era of increasing disturbances to natural environments.Co-diversification, the simultaneousdiversification of hosts and symbionts,represents the most definitive and empirical testof shared evolutionary historywithinholobiont assemblages.However, detectingco-diversifiedsymbiontsinfluencingholobiont phenotype remains difficult, particularly in wild animalsharboringcomplex microbial communities andliving in logisticallychallenging ecosystems like the oceans—ironically, the environmentsmost profoundly affectedby current global changes.Understanding ecological and evolutionary interdependence withinmarine holobiontsrequiresto focuson low-complexitymicrobiomesassociated with hosts with a well-known population structure, and genetic and evolutionary trajectory.Wepropose a comprehensive approach that combinesmultigenic metabarcoding with phylogenetic congruencyanalysesacrossvariousmicrobial organizational levels—ranging from community to symbiont microdiversity—to elucidateco-diversification patternswithinmarine invertebrate holobionts.We aim to characterize the microbiomes associated with the true limpet Nacella, an attractive mollusk model of the Southern Ocean, and assess the degree of interdependence by examining the influence of host historical biogeography on symbiont ...